2017
DOI: 10.1007/s10456-017-9552-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenesis for cancer revisited: Is there a role for combinations with immunotherapy?

Abstract: Angiogenesis is defined as the formation of new blood vessels from pre-existing vessels, and has been characterized as an essential process for tumor cell proliferation and viability. This has led to the development of pharmacological agents for anti-angiogenesis to disrupt the vascular supply and starve tumor of nutrients and oxygen, primarily through blockade of VEGF/VEGFR signaling. This effort has resulted in 11 anti-VEGF drugs approved for certain advanced cancers, alone or in combination with chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
413
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 531 publications
(449 citation statements)
references
References 202 publications
(187 reference statements)
2
413
0
10
Order By: Relevance
“…In order to achieve this, the histopatho-logical evaluations of the tumor vasculature as described here must be supplemented by medical imaging techniques and/or assays, which utilize small biopsies, circulating tumor cells, endothelial cells, or circulating tumor derivatives. Moreover, the importance of an accurate biomarker of ongoing sprouting angiogenesis or non-angiogenic vessel co-option is corroborated by the extensively documented and strong link between angiogenesis and immune suppression [129–131] and the surge of clinical studies that combine anti-VEGF and immunotherapy strategies [132]. In this regard, studies suggested that interactions between endogenous galectins and glycans may link tumor immunosuppression and angiogenesis, conferring resistance to anti-VEGF treatment [133].…”
Section: Tumor Microvessel Density and Histopathological Growth Patmentioning
confidence: 99%
“…In order to achieve this, the histopatho-logical evaluations of the tumor vasculature as described here must be supplemented by medical imaging techniques and/or assays, which utilize small biopsies, circulating tumor cells, endothelial cells, or circulating tumor derivatives. Moreover, the importance of an accurate biomarker of ongoing sprouting angiogenesis or non-angiogenic vessel co-option is corroborated by the extensively documented and strong link between angiogenesis and immune suppression [129–131] and the surge of clinical studies that combine anti-VEGF and immunotherapy strategies [132]. In this regard, studies suggested that interactions between endogenous galectins and glycans may link tumor immunosuppression and angiogenesis, conferring resistance to anti-VEGF treatment [133].…”
Section: Tumor Microvessel Density and Histopathological Growth Patmentioning
confidence: 99%
“…Several cytokines, including VEGF, VEGF‐C, VEGF‐D, bFGF, and HGF, play a crucial role during tumor growth and angiogenesis . Inhibition of VEGF by upstream targets or neutralizing antibodies could efficiently inhibit tumor growth and cancer cell metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that DANCR was upregulated Several cytokines, including VEGF, VEGF-C, VEGF-D, bFGF, and HGF, play a crucial role during tumor growth and angiogenesis. 22,23 Inhibition of VEGF by upstream targets or neutralizing antibodies F I G U R E 6 miR-145 plays a necessary role during DANCR promoting angiogenesis in ovarian cancer. A, Real-time determination of miR-145 expression in miR-Ctrl and miR-145 transfected A2780 cells (n = 4, **P < .01).…”
Section: Discussionmentioning
confidence: 99%
“…Among various pro-angiogenic factors, vascular endothelial growth factor (VEGF) is the most influential factor responsible for promoting tumor angiogenesis despite the nature and origin of tumor. Thus, VEGF targeting has efficacy in several cancer management (3,4). Rapid tumor cell proliferation creates hypoxia or oxygen deficit (5) and stabilizes HIF1α, the main VEGF regulator along with growth factors and oncogenes (6,7).…”
Section: Introductionmentioning
confidence: 99%